ANALISIS SISTEM PENGENDALIAN INTERNAL PEMUNGUTAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN DALAM OPTIMALISASI PENERIMAAN RETRIBUSI DAERAH KOTA MAKASSAR - Hasmawati Hasmawati (Jurnal Administrasi Terapan, 2022)
This study aims to analyze the internal control system applied by the government related to the collection of building permit levy. Data collection is done through literature study, documentation and interview. The method used is descriptive-qualitative method.The results of this study indicate that the internal control system of Makassar City government in levies of building permit permit has not fulfilled the elements of internal control system according to Government Regulation number 60 Year 2008 because there are still some weakness or non-conformity.The results suggest that DPMPTSP of Makassar City to analyze target determination every year is expected to firstly analyze the potential to be gained and further improve the quality of service by accelerating the completion of the application file process. Furthermore DPMPTSP Makassar City must hold cooperation with the village and sub-district to socialize the community about the importance of IMB. Keywords: Internal Control System, Building Permit License,Acceptance of Levies.